Issues in Women's Land Rights in Cameroon - Fonjong, Lotsmart N. (Book collections on Project MUSE., 2012)
This book explores the customary, social, economic political and rights issues surrounding access, ownership and control over land from a gender perspective. It combines theory and practice from researchers, lawyers and judges..